2004
DOI: 10.1242/jcs.00936
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filaments are dynamic and motile elements of cellular architecture

Abstract: Recent evidence showing that intermediate filaments (IFs) are dynamic, motile elements of the cytoskeletal repertoire of vertebrate cells has overturned the long-standing view that they simply form static `space filling' cytoplasmic networks. In fact, many types of IF are now known to engage in a remarkable array of movements that are closely associated with their assembly, disassembly and subcellular organization. Some of these motile properties are intrinsic to IFs and others are attributable to molecular cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
191
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(206 citation statements)
references
References 88 publications
11
191
1
3
Order By: Relevance
“…Thus, it was unanticipated that in Vim KO astrocytes the principal effect of low WFA concentrations is to facilitate the extension of short GFAP squiggles into their long filamentous forms. These GFAP squiggles found in Vim KO astrocytes have been previously reported (34) and resemble the IF precursors described in spreading cells (35). Moreover, this phenomenon reflects a functional deficiency of vimentin (36), because transfection of GFAP into vimentindeficient SW13 cells or into Vim KO astrocytes, but not WT astrocytes, was also reported to produce the short GFAP squiggles (27).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Thus, it was unanticipated that in Vim KO astrocytes the principal effect of low WFA concentrations is to facilitate the extension of short GFAP squiggles into their long filamentous forms. These GFAP squiggles found in Vim KO astrocytes have been previously reported (34) and resemble the IF precursors described in spreading cells (35). Moreover, this phenomenon reflects a functional deficiency of vimentin (36), because transfection of GFAP into vimentindeficient SW13 cells or into Vim KO astrocytes, but not WT astrocytes, was also reported to produce the short GFAP squiggles (27).…”
Section: Discussionsupporting
confidence: 78%
“…The filament assembly first step entails the lateral annealing of tetramers into unit length filaments (ULFs) with longitudinal annealing of two ULFs, followed by a second step involving the longitudinal annealing of an ULF to the end of a filament and the final step of end-to-end annealing of two filaments. The detection of ULFs as dots and their fusion products that give rise to squiggles has been now confirmed also in vivo (35). On the one hand, our findings showing a dispersion of ϳ2-m long GFAP particle-like structures in control Vim KO retina, which are considerably larger than 60 nm ULFs (41), would argue that GFAP precursors have undergone the initial step of filament assembly to form squiggles.…”
Section: Discussionsupporting
confidence: 77%
“…32 Recent studies, based on a variety of different cell types, have revealed that IFs are remarkably dynamic and exhibit a complex array of motile activities related to their subcellular assembly and organization. 33 Vimentin interacts directly with several organelles, membrane or cytoskeleton associated proteins as well as cellular compartments for which linker proteins remain to be defined. 5 Vimentin could also link extracellular and cytoplasmic events to the nucleus through interaction with a multitude of bindings partners.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in vivo the various vimentin and keratin precursors are motile due to their associations with microtubule [28] and actin filament based motors [25] ••. Importantly, their motile properties are required for their proper assembly into the extensive IF networks that typify interphase cells [19,24,25].…”
Section: (••)mentioning
confidence: 99%